Managing projects in organizations : - Frame, J. Davidson (Jossey-Bass Publishers, 1995)
Sound advice for product, engineering, and service-based oganizations. Unlike other project management books that focus on engineering and manufacturing settings alone, this resource encompasses product, engineering, and service-based organizations. Plus, it covers important new developments in software, outsourcing, quality, and related issues. Much more than a mere checklist of techniques, Managing Projects in Organizations provides you with a sound, overall methodology for dealing with information-age projects. You get advice on overcoming problems at the organizational, team and individual levels, managing human resources, selecting the best team structure, identifying customer needs, defining project requirements, and managing the inevitable politics every project presents, plus much, much more!